2004
DOI: 10.1111/j.1395-3907.2004.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age, sex, race, refractive error and optic disc parameters on the sensitivity and specificity of scanning laser polarimetry

Abstract: ABSTRACT.Purpose: To evaluate the influence of age, sex, race, refractive error and optic disc topography on the sensitivity and specificity of scanning laser polarimetry (SLP) in the diagnosis of glaucoma. Methods: A total of 88 normal individuals and 95 glaucoma patients were included in this study. Glaucoma was defined on the basis of both optic nerve damage and visual field defects. Scanning laser polarimetry, optic disc topography, automated perimetry and refractometry were performed in all subjects. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…1 In particular, individuals of African descent have been shown to have an increased prevalence of primary open-angle glaucoma and have poorer visual outcomes. [2][3][4][5][6] Racial and ethnic differences in optic nerve head (ONH) parameters and retinal nerve fiber layer (RNFL) thickness have been described [7][8][9][10][11][12][13][14][15][16] using scanning laser polarimetry, 7,8 confocal scanning laser ophthalmoscopy, [9][10][11][12][13][14][15][16] and time-domain optical coherence tomography (OCT). 15,16 Disc area (DA) is larger in individuals of African descent than in any other racial or ethnic group.…”
mentioning
confidence: 99%
“…1 In particular, individuals of African descent have been shown to have an increased prevalence of primary open-angle glaucoma and have poorer visual outcomes. [2][3][4][5][6] Racial and ethnic differences in optic nerve head (ONH) parameters and retinal nerve fiber layer (RNFL) thickness have been described [7][8][9][10][11][12][13][14][15][16] using scanning laser polarimetry, 7,8 confocal scanning laser ophthalmoscopy, [9][10][11][12][13][14][15][16] and time-domain optical coherence tomography (OCT). 15,16 Disc area (DA) is larger in individuals of African descent than in any other racial or ethnic group.…”
mentioning
confidence: 99%
“…Each technology—scanning laser polarimetry, optical coherence tomography, confocal laser scanning ophthalmoscopy—has its strengths and limitations. There are increasing reports in the literature on the effect of disease states on measurement variability 1 2…”
mentioning
confidence: 99%
“…The ability to detect glaucoma with VF defects was moderately strong at best: sensitivity and specificity were 82% and 83%, respectively, in a study by Costa et al, 38 and sensitivity was 64% at a fixed specificity of 95% in a study by Galvao Filho et al 41 The 6 articles on GDx VCC reported excellent correlation with glaucoma diagnosis (Bowd III, 35 Essock I, 40 Medeiros II-IV [43][44][45] Four of the 5 studies comparing GDx FCC with VCC revealed better discriminate function with VCC (Bowd II, 36 Brusini et al, 37 Schlottmann et al, 49 Weinreb et al 50 ). The use of VCC significantly improved detection of glaucoma (Brusini et al, Weinreb et al) and correlation with VF loss (Boyd II, Schlottmann et al).…”
Section: How Well Does the Device Aid In Glaucoma Diagnosis Particulmentioning
confidence: 99%
“…Five of the 16 studies compared GDx VCC with GDx FCC for detecting glaucoma (Bowd II, 36 Brusini et al, 37 Da Pozzo et al, 39 Schlottmann et al, 49 Weinreb et al 50 ). Five studies addressed only GDx FCC's ability to discern glaucomatous damage (Costa et al, 38 Galvao Filho et al, 41 Horn et al, 42 Mohammadi et al, 46 Munkwitz et al 47 ), and the remaining 6 studies evaluated GDx VCC only (Bowd III, 35 Essock I, 40 Medeiros II-IV, [43][44][45] Reus and Lemij 48 ). All articles except 4 (Bowd II, 36 Medeiros IV, 45 Mohammadi et al, 46 Munkwitz et al 47 ) used a definition of glaucoma that required a VF defect at baseline.…”
Section: How Well Does the Device Aid In Glaucoma Diagnosis Particulmentioning
confidence: 99%